DRAINAGE, RAINWATER HARVESTING, AND RIVER REHABILITATION DESIGN OF JIMBARAN RESORT, BALI - IZZATU AMATULLAH, SALMA
Bali has rapidly growing tourism potential. This tourism potential needs to be supported by the provision of supporting facilities that support a pleasant travel experience for tourists. To support the development of tourism of Bali, it is planned to build a resort in Jimbaran, Bali. In the construction of the resort, a surface drainage system, rainwater harvesting, and river rehabilitation are planned. The design rainfall was analyzed using the Normal Distribution Method. In the drainage planning, a 10-year return period of 146,0 mm of rain is used. In calculating the drainage channel, the Rational Method is used to obtain the design discharge and the Manning Method is used to obtain the dimensions of the channel. The channel used has a rectangular cross section with concrete material with the largest channel dimensions reaching 100 cm x 120 cm. In the resort area, rainwater storage is also planned with a capacity of 3000 and 6000 liters and can meet 64% and 67% for each type of cottage. In planning the scour protection (riprap) a 50 year return period of rain of 183,0 mm is used. The planned flood discharge used the Nakayasu Method with a peak discharge 33,1 m3/s. The dimensions of the riprap are planned based on water level elevation and flow velocity during flooding, which are modeled using HEC-RAS. The modeling results show that the maximum flow velocity during flooding reaches 3,5 m/s with a maximum elevation of +3,42 m. The budget plan for construction is Rp. 7.150.000.000.000,00 and operating and maintenance costs are Rp. 400.000.000,00/year.